What International Advice Do Universities Need? - Altbach, Philip; Salmi, Jamil (International Higher Education, 2012)
International advisory committees are a new development globally. Some universities seeking to raise their profile and improve their performances have implemented committees of prominent academics and business people to provide advice. These committees need to be effectively organized if they are to have a useful impact.